ChemInform Abstract: A Concise One‐Pot Organo‐ and Biocatalyzed Preparation of Enantiopure Hexahydrofuro[2, 3‐b]furan‐3‐ol: An Approach to the Synthesis of HIV Protease Inhibitors. Issue 34 (4th August 2016) - Kanemitsu, Takuya; Inoue, Mizuho; Yoshimura, Nono; Yoneyama, Kazutoshi; Watarai, Rie; Miyazaki, Michiko; Odanaka, Yuki; Nagata, Kazuhiro; Itoh, Takashi
Abstract: The one‐pot synthesis of the title species (IV) involves condensation of dihydrofuran with glycolaldehyde dimer (II) followed by lipase‐catalyzed kinetic resolution.